Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1103/physrevlett.103.246803
|View full text |Cite
|
Sign up to set email alerts
|

Cloaking from Surface Plasmon Polaritons by a Circular Array of Point Scatterers

Abstract: In recent years it has been demonstrated both theoretically and experimentally that it is possible to cloak a predefined region of space from interaction with external volume electromagnetic waves, rendering an arbitrary object inside this region invisible to an outside observer. The several strategies that have been developed for achieving such cloaking cannot be applied directly to the cloaking of a surface feature from surface plasmon polaritons propagating on that surface. Here we demonstrate that it is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…In 2008, Smolyaninov et al achieved a noticeable reduction in the scattering of SPPs incident upon a cloak consisting of polymethylmethacrylate (PMMA) at a wavelength of 532 nm [19,20] . More recently, Baumeier et al demonstrated theoretically that it is possible to reduce signifi cantly the scattering of an object by an SPP at a wavelength of 633 nm when it is surrounded by two concentric rings of point scatterers [21] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Smolyaninov et al achieved a noticeable reduction in the scattering of SPPs incident upon a cloak consisting of polymethylmethacrylate (PMMA) at a wavelength of 532 nm [19,20] . More recently, Baumeier et al demonstrated theoretically that it is possible to reduce signifi cantly the scattering of an object by an SPP at a wavelength of 633 nm when it is surrounded by two concentric rings of point scatterers [21] .…”
Section: Introductionmentioning
confidence: 99%
“…4]. The practical interest in devising the cloaking devices is no longer confined to the electromagnetic waves [62][63][64][65][66][67][68][69][70][71][72], but has also imbued the similar quest related with the acoustic waves [73][74][75][76][77][78][79][80][81][82][83][84][85] and the plasmonic waves [86][87][88][89][90][91][92][93][94][95][96][97][98]. The cloakmania has gone to the extent that some scientists think that all the attention paid to cloaking phenomenon distracts us from the technology's true potential: anything that makes use of the electromagnetic spectrum might be improved or altered!…”
Section: Fig 2: (Color Online)mentioning
confidence: 99%
“…By leaking electromagnetic energy along the structure, the radiated beams of LWAs can scan in the space as frequency changes [2]. Frequency beam scanning antennas are widely used in radar and wireless communication systems [3][4][5]19].…”
Section: Introductionmentioning
confidence: 99%